Application Of Fuzzy-Logic In Ship Manoeuvring In Confined Waters - Surendran, S.; Lee, S. K (Sustainable Marine Structures, 2019)
A ship manoeuvring problem is solved using an algorithm built on fuzzy logic. The manoeuvring model for a design ship is coded in C++ and the results are presented here. A bulk carrier is assumed as design ship for a newly setting up harbor along the east coast of India. The harbor mouth is 25 km away from the deep water zone. The approach channel is straight along the 22 km length. Laterally restricted and shallow waters are considered and their influences on hydrodynamic derivatives are discussed. Some sample problems are solved. Trajectories, ship heading, rudder angle, velocities and accelerations, of the moving vessel, are calculated and presented for clarity. The developed code is robust in the sense that any designer or user can easily interact with various input parameters to verify the outputs and their suitability for the design ship meant for a particular water front location. The results are validated using another algorithm built on PID which is discussed in brief. ER